Analisis Nilai Sosial Dalam Buku “Cerita Rakyat Nias” Karya Sadieli Telaumbanua dan Berliana Siagawati Waruwu - Dewi Murni Hartati Nazara; Noveri Amal Jaya Harefa (Indo-MathEdu Intellectuals Journal, 2023)
Literature is a form of creative and productive human expression in the form of experiences, thoughts, feelings in producing a work or idea and the spirit has aesthetic value and is able to reflect forms of social reality for society. Literary works are created to convey certain messages that have deep meaning, and their existence cannot be separated from socio-cultural problems in everyday life. The problem in this study is the meaning and value contained in the book "Folk Stories of Nias" by Sadieli Telaumbanua and Berliana Siagawati Waruwu. The purpose of this research is to seek and find social values ​​in the book "Folk Stories of Nias" by Sadieli Telaumbanua and Berliana Siagawati Waruwu, especially social values: material, vital and spiritual. The method used in this study is a qualitative research method based on literature. To analyze data there are three stages, namely reduction, presentation, and conclusion. Based on the research results, three social values ​​were found, namely (1) material values, (2) vital values, (3) spiritual values